Integration of Islamic Values ​​in Science Education 'A Reconstruction Effort in Education': Integrasi Nilai-Nilai Islam Dalam Pendidikan Sains ‘Sebuah Upaya Rekonstruksi dalam dunia Pendidikan’ - Wahyuni, Akhtim (Universitas Muhammadiyah Sidoarjo, 2020)
Islam and science are an inseparable unity. Islam as a religion is a source of knowledge and knowledge is a means to apply everything contained in religious teachings. In the Qur'an, there are around 750 verses related to science. This shows that Islam places great emphasis on the development of science. But what happens, these two things are pushed aside from each other, resulting in a dichotomy of knowledge that enters all aspects of life. The awareness to restore the position of Islam and science began to be rolled back by Muslim thinkers by integrating the two. In educational institutions, the integration of Islamic and science values ​​is strengthened through an